2007
DOI: 10.1063/1.2431576
|View full text |Cite
|
Sign up to set email alerts
|

In situ laser microprocessing of single self-assembled quantum dots and optical microcavities

Abstract: The authors employ a focused laser beam both as a probe and as a local heat source to tune in situ, over a broad range and with resolution-limited accuracy, the quantized energy states of single optical microcavities and self-assembled quantum dots (QDs). The approach is demonstrated by bringing an optical mode of a microdisk into resonance with the emission of a single QD and by tuning spatially separated QDs in mutual resonance. This processing method may be used, e.g., to fabricate arrays of perfectly reson… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 16 publications
0
50
0
Order By: Relevance
“…Another tuning technique that relies on locally heating microcavities to permanently change the structure of the resonator and the QDs has been reported by Rastelli et al 15 In conclusion, we have demonstrated a technique for in situ tuning of QDs by up to 1.4 nm without significant deterioration in the QD emission. This method works locally and reversibly, making it a useful tool for a range of solid-state studies, from local thermometry to quantum information science.…”
Section: -2mentioning
confidence: 82%
“…Another tuning technique that relies on locally heating microcavities to permanently change the structure of the resonator and the QDs has been reported by Rastelli et al 15 In conclusion, we have demonstrated a technique for in situ tuning of QDs by up to 1.4 nm without significant deterioration in the QD emission. This method works locally and reversibly, making it a useful tool for a range of solid-state studies, from local thermometry to quantum information science.…”
Section: -2mentioning
confidence: 82%
“…Recent experiments have demonstrated the possibility of irreversible tuning of the modes by using digital etching, 5 scanning probe microscopy assisted oxidation 6 and laser-assisted oxidation 7 or of reversible tuning by gas absorption 8 and laser heating. 9,10 All these methods allow tuning of the cavity modes either on the blue or on the red side, while a complete control of the resonant wavelength requires some combination of different methods.…”
Section: Introductionmentioning
confidence: 99%
“…While deterministic approaches for a highly matched spatial arrangement of emitter and cavity have been demonstrated [8,[23][24][25], the spectral matching at a given temperature needs post fabrication tuning of either the QD transition or the cavity mode. An in-situ manipulation of the QD transition energy has been performed by temperature variation [26], electric fields [27], local heating [28], and laser annealing [29]. For photonic crystal defect cavities [8,[30][31][32][33] and microdisk structures [29,34], precise reversible and irreversible tuning mechanisms have been developed using either surface etching, desorption or deposition.…”
Section: Introductionmentioning
confidence: 99%